The Migration of Europeans to the United States at the Middle of the 19th Century – the Irish and German Wave - Sorin-Stefan Maha (CES Working Papers, 2011)
This article analyses the contribution of the second wave of immigrants to the United States to the formation of the young American people. Unlike other states, the USA is a nation founded on waves of immigrants coming from different parts of the world. This paper includes the second wave of immigrants in US history in the four waves and presents the migration of the Irish and Germans to the USA at the middle of the 19th century. They had an important contribution to the increase of American population and were a source of consumption and workforce for agriculture and various industries.
Keywords: J11; N31; N33; 330; immigration; Irish immigrants; German immigrants; potato crisis Romania